Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1097/ju.0000000000003159
|View full text |Cite
|
Sign up to set email alerts
|

Use of Monitoring Tests Among Patients With Localized Prostate Cancer Managed With Observation

Abstract: Purpose:It is unknown whether compliance with recommended monitoring tests during observation of localized prostate cancer has changed over time.Materials and Methods:We performed a retrospective cohort study of Medicare beneficiaries diagnosed with low- or intermediate-risk prostate cancer in 2004-2016 who were initially managed with observation for a minimum of 12 months. The primary objective was to examine rates of PSA testing, prostate biopsy, and prostate MRI. We used multivariable mixed effects Poisson … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Leapman et al (page 710) present a retrospective cohort multicenter study of Medicare beneficiaries diagnosed between 2004 and 2016 and initially managed with observation for at least 12 months. 4 In those patients followed without treatment for at least 5 years, only 48% had any additional prostate biopsies and 31% had 1 prostate MRI. Accepting that patient preference and clinical factors including age and risk are central to the decisions around intensity of monitoring, some of the other observations from the authors point to ongoing sociodemographic disparities in the delivery of guideline-concordant care.…”
Section: Variation In Monitoring Patients For Lower-risk Prostate Cancermentioning
confidence: 96%
“…Leapman et al (page 710) present a retrospective cohort multicenter study of Medicare beneficiaries diagnosed between 2004 and 2016 and initially managed with observation for at least 12 months. 4 In those patients followed without treatment for at least 5 years, only 48% had any additional prostate biopsies and 31% had 1 prostate MRI. Accepting that patient preference and clinical factors including age and risk are central to the decisions around intensity of monitoring, some of the other observations from the authors point to ongoing sociodemographic disparities in the delivery of guideline-concordant care.…”
Section: Variation In Monitoring Patients For Lower-risk Prostate Cancermentioning
confidence: 96%
“…3 Prostate MRI has been rapidly incorporated into clinical practice in multiple contexts, including prior to prostate biopsy, as a tool for local staging and as a component of active surveillance. 4,5 Although there is much information available regarding the diagnostic and prognostic accuracy of prostate MRI, little is known about patient experiences with and knowledge of MRI imaging and its role in their treatment decision-making. 6,7 Prior observational studies have found that use of prostate MRI is associated with increased use of initial observational management of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of The Journal, Leapman and colleagues (page 710) sought to assess clinical trends in follow-up testing over the last 15 years. 4 Using Surveillance, Epidemiology, and End Results–Medicare data from 2004-2016, the authors identified patients diagnosed with low- or intermediate-risk prostate cancer who did not undergo treatment of their cancer within 12 months of diagnosis. This population was considered to be managed with observation, and the number of PSA tests and prostate biopsies performed during follow-up were assessed, along with demographic factors and socioeconomic status.…”
mentioning
confidence: 99%